2021
DOI: 10.3390/ijgi10040215
|View full text |Cite
|
Sign up to set email alerts
|

BIM Adoption in the Cambodian Construction Industry: Key Drivers and Barriers

Abstract: Critical issues surrounding the promotion and adoption of building information modeling (BIM) for construction projects are largely country-specific due to contextual socio-cultural, economic, and regulatory environments impacting construction operations and outcomes. There is little information on BIM adoption issues specific to the Cambodian construction industry (‘the industry’). This paper aims to narrow existing knowledge by investigating key drivers for, and barriers to the adoption of BIM in the industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…In future, building information modelling (BIM) will also have a significant impact on the work of surveyor engineers, as it is currently regarded as a major paradigm shift in the construction industry, especially for civil engineers and architects [31]. Traditional building design models depend to a large extent on two-dimensional technical drawings, and a BIM platform expands the three primary spatial dimensions (width, height and depth), integrating multiple advantages due to their economic benefits in design and construction phases [32,33]. Future perspectives include the establishment and integration of the site layout plan with the BIM design in order to achieve sustainable and productive practice regarding the construction industry.…”
Section: Discussionmentioning
confidence: 99%
“…In future, building information modelling (BIM) will also have a significant impact on the work of surveyor engineers, as it is currently regarded as a major paradigm shift in the construction industry, especially for civil engineers and architects [31]. Traditional building design models depend to a large extent on two-dimensional technical drawings, and a BIM platform expands the three primary spatial dimensions (width, height and depth), integrating multiple advantages due to their economic benefits in design and construction phases [32,33]. Future perspectives include the establishment and integration of the site layout plan with the BIM design in order to achieve sustainable and productive practice regarding the construction industry.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to the complexity and time-consuming calculations of the value of S, Kendall's coefficient of concordance is computed by the Statistical Packages for Social Sciences (SPSS) computer software (similarly to other scholars [67][68][69]).…”
Section: Delphi Survey Techniquementioning
confidence: 99%
“…Luxury businesses in the vicinity of ordinary businesses R 68 Poor wide advertising R 69 Ignorance of security and safety protocol R 70 Lack of crisis management in CRCBPs R 71 Lack of specific instructions in case of unexpected events R 72 Lack of maintenance team stationed in the CRCBs R 73 Adjacent building condition R 74 Historical conditions…”
Section: R 67mentioning
confidence: 99%
“…Previous studies have identified the driving forces and constraints to the adoption of diverse technologies in the construction industry [ 10 , 41 ]. More specifically, these technologies can improve project performance concerning cost–time performance, productivity, and safety performance.…”
Section: Literature Reviewmentioning
confidence: 99%